Optimal thickness of cipp liners used in trenchless sewer rehabilitation - Kuliczkowski, Andrzej (Instal, 2020)
The aim of the article is to determine the impact of various factors on the thickness of rehabilitation liners in CIPP technology, which is currently the most commonly used in trenchless rehabilitation of sewage pipelines. Problems concerning the influence of the following factors on the thickness of rehabilitation liners are presented: stiffness of the pipe, E-modulus, groundwater table, rehabilitated pipe material and the type of resin used. Recommendations have been formulated to improve the current methods of designing resin liners.